The interference characteristics of light-waves from a tilted and defocused cat-eye optical lens irradiated by laser beam - Zhao, Yanzhong; Sun, Huayan; Zhang, Xi; Wang, Yong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
When a tilted and defocused cat-eye optical lens is irradiated by laser beam, the reflected light-waves can be regarded as an off-axis spherical wave. Based on this idea and the theory of angular spectrum, our research has been directed towards some formulas describing the interference of the cat-eye reflected light with the reference incidence light. Through numerical computation, relationships governing the variation of the interference characteristics with parameters including the incidence angle, the tilted angle of the moving mirror, and the focal shift, are established. The relationships are experimentally validated. Our results have shown that the interference circles gradually move outwards, and the spot profile becomes broken with the increase of the incidence angle, the coordinates of the curvature center of the interference fringes are proportional to the incidence angle and the tilted angle of the moving mirror, the number of the interference fringes becomes larger along with the increase of the focal shift and the tilted angle of the moving mirror. The results can be used to estimate the tilted state of the cat-eye target.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 617-630
Keywords: optyka; interference characteristics; cat-eye effect; tilted and defocused cat-eye optical lens; incidence angle